Single Machine CON/SLK Due Date Assignment Scheduling with Controllable Processing Time and Job-dependent Learning Effects. (29th December 2017) - Wang, Ji-Bo; Geng, Xin-Na; Liu, Lu; Wang, Jian-Jun; Lu, Yuan-Yuan
Abstract: This paper addresses resource allocation scheduling problems with CON/SLK due date assignment and job-dependent learning effects on a single machine. Two different resource consumption functions under common (denoted by CON) and slack (denoted by SLK) due date assignment are considered. The objective is to determine the optimal due dates of jobs, a sequence for jobs and resource allocation of jobs to minimize a total cost function. The optimality properties for all problems and polynomial time algorithms are proposed to solve these problems.